Bridging Imagination and Reality: Value Co-Creation and Interactive Storytelling in Bali's Marketing - Putri Ekaresty Haes; I Putu Yoga Purnama Wijaya; Ni Made Dhian Rani Yulianti; Sahri Aflah Ramadiansyah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines how interactive storytelling functions as an operational mechanism of value co-creation within the digital marketing practices of Bali's tourism industry. In an increasingly competitive digital environment, tourism brands must move beyond one-way promotional messages and shift toward collaborative narrative experiences that actively involve consumers. This research aims to analyze how tourism actors in Bali design and implement interactive storytelling to strengthen engagement, enhance experiential value, and build destination competitiveness. Employing a qualitative case study method, data were gathered through observations, detailed interviews with five key informants, and an analysis of digital campaign documents. The analysis employed the Miles and Huberman framework, supported by data triangulation to ensure validity. The research is based on the Value Co-Creation theory by Prahalad and Ramaswamy, along with the Service-Dominant Logic proposed by Vargo and Lusch, which views consumers as active participants in creating meaning and experiences. The findings reveal that interactive storytelling enables consumers to become protagonists in destination narratives through participatory content, user-generated storytelling, and technology-driven interactions. However, several challenges persist, including cultural sensitivity issues, limited technological capabilities, algorithmic constraints, and budget limitations for high-quality content creation. The study concludes that interactive storytelling offers a powerful strategy to enhance emotional engagement, strengthen brand identity, and create personalized tourism experiences that support long-term loyalty.